Input of solid‐state 13 C NMR to study permeation of wet archaeological bones by dicarboxylic fatty diacid‐based chemicals - Chaumat, Gilles; Duval, Florent; Blinder, Rémi; Bayle, Pierre‐Alain; Bardet, Michel (Magnetic resonance in chemistry, 2020)
Conservation treatment of degraded archaeological osseous materials is still an open challenge, since no specific conservation protocol is currently available for restorers or museum curators. This work aims to test the efficiency of two original consolidant solutions in consolidating archaeological material. Archaeological osseous materials remain rare and sparsely available, it is a real drawback for optimization of conservation treatments, therefore in the present work a set of representative samples was chosen. The consolidants tested were a solution of disodium sebacate and a novel polyalcohol (SG1.2) obtained by esterification of 5 succinic diacids with 6 molecules of glycerol at 150°C. Characterization studies of archaeological bones, combining SEM microscopy, IR spectroscopy and high‐resolution solid‐state 13 C NMR investigations, have been carried out to assess the effective permeation of bone by the consolidant solutions and to determine their chemical interactions with the residual components of archaeological bones. Although both water solutions significantly impregnate bone, we show that, the solution with disodium sebacate leads to chemical attack on the mineral component due to preferential precipitation of endogenous calcium by the sebacate ions. Such deleterious behaviour is not observed at all with the SG1,2 chemicals. The added value of the polyalcohol treatment as strengthening agent suitable for archaeological bony materials should be further demonstrated by mechanical and ageing tests.